CALA: Cumulative Volume of Calcified Lesions of the Aorta in Cardiac Surgery - Ioannou, Stelios; Braun, Christian; Hartrumpf, Martin; Kühnel, Ralf-Uwe; Vafa, Ali; Schröter, Filip; Albes, Johannes (The Thoracic and Cardiovascular Surgeon, 2022)
One of the major key questions raised in this retrospective study was to identify any correlation of atherosclerotic plaque volume of the ascending aorta and aortic arch with adverse events such as postoperative stroke, critical illness polyneuropathy and myopathy, as well as delirium and all-cause in-hospital mortality. In a second phase of this study, we investigated the relationship between atherosclerotic plaque volume and adverse events regarding the construction of proximal anastomosis on coronary artery bypass grafting procedures using different clamping techniques such as construction of anastomosis on cross-clamping or cross-clamping plus consecutive partial clamping of the aorta. The key findings of our research were that the size of calcium lesions of the ascending aorta and aortic arch correlates with early mortality, critical illness polyneuropathy/myopathy, and delirium but not with stroke. On the other hand, there were no significant differences between isolated cross-clamping versus cross-clamping plus consecutive partial clamping of the aorta regarding the primary adverse events by means of mean plaque volume.
Keywords: atherosclerosis; aorta/aortic; stroke; outcomes; includes mortality; morbidity